2023
DOI: 10.1039/d3ob01349a
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-free regioselective direct acylation of quinazolines for the synthesis of acylquinazoline derivatives

Wei Chen,
Jingjun Fang,
Jian Huang
et al.

Abstract: An efficient method for direct regioselective acylation of quinazolines under metal-free conditions was developed. The acylation reaction of quinazolines gave corresponding acyl quinazolines in ethyl acetate with good to excellent yields and excellent functional group tolerance and site selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…27 For example, recently, Peng et al reported direct acylation of quinazolines in the presence of PhI(OCOCF 3 ) 2 and TMSN 3 without any transition metal catalyst. 28 Encouraged by these developments and our persistent studies on the modification of purines, 29 we tried to develop a green, metal-free, light-free radical reaction to synthesize C 6 -acylated purines via Minisci-type reaction (Scheme 1F).…”
Section: Introductionmentioning
confidence: 99%
“…27 For example, recently, Peng et al reported direct acylation of quinazolines in the presence of PhI(OCOCF 3 ) 2 and TMSN 3 without any transition metal catalyst. 28 Encouraged by these developments and our persistent studies on the modification of purines, 29 we tried to develop a green, metal-free, light-free radical reaction to synthesize C 6 -acylated purines via Minisci-type reaction (Scheme 1F).…”
Section: Introductionmentioning
confidence: 99%